Cycling stability of ultrafine β-Ni(OH)2 nanosheets for high capacity energy storage device via a multilayer nickel foam electrode. (1st September 2016) - Mao, Yuqiong; Li, Taotao; Guo, Chunli; Zhu, Fuchun; Zhang, Chunchen; Wei, Yinghui; Hou, Lifeng
Abstract: Ultrafine β-Ni(OH)2 nanosheets with an average diameter of about 14.5 nm have been fabricated by immersing Na(HCO3 )2 nanoparticles into 6 M KOH solution. The multilayer nickel foam system was introduced to improve the cycling stability of ultrafine β-Ni(OH)2 nanosheets without using acetylene black. The results demonstrated that the specific discharge capacity of the β-Ni(OH)2 electrode was up to 524.5C g −1 at 5 A g −1 and retained 83.8% after 1000 cycles, which was better than those of other β-Ni(OH)2 electrodes obtained using acetylene black as conductors (retained 59.1% after 1000 cycles). Even after 5000 cycles, the specific capacity also maintained 80.8%. In addition, a hybrid supercapacitor was successfully fabricated based on ultrafine β-Ni(OH)2 nanosheets and active carbon, the corresponding energy density and power density at 0.1 A g −1 were calculated to be 20.45 Wh kg −1 and 75 W kg −1, respectively. What's more, the hybrid supercapacitor could light up a set of low-voltage light-emitting diodes.